Factors determining fatigue in the chronic fatigue syndrome: a path analysis. Issue 5 (2nd September 2016) - Tobback, Els; Hanoulle, Ignace; Mariman, An; Delesie, Liesbeth; Pevernagie, Dirk; Vogelaers, Dirk
Abstract: Objectives: To explore the interrelationship of different dimensions (fatigue, neuroticism, sleep quality, global mental and physical health) in patients with chronic fatigue syndrome (CFS). Methods: Patients meeting the Fukuda criteria of CFS filled out two independent fatigue scales (Fatigue Questionnaire, FQ and Checklist Individual Strength, CIS), NEO-Five Factor Inventory (NEO-FFI), Pittsburgh Sleep Quality Index (PSQI) and Medical Outcomes Study 36-item Short Form Health Survey (SF36). Exploratory and confirmatory path analyses were performed. Results: Out of 226 eligible patients, 167 subjects were included (mean age 39.13 years, SD 10.14, 92% female). In a first exploratory path analysis, using FQ for assessment of fatigue, night-time PSQI sleep quality had a direct effect on SF36 physical quality of life (PQoL) and no effect on FQ fatigue. This was confirmed by a subsequent path analysis with CIS fatigue and by confirmatory path analyses in 81 patients. These unexpected results raised the question whether FQ or CIS fatigue sufficiently operationalizes fatigue in CFS patients. Conclusions: Poor sleep quality seems to directly impact on mental quality of life (MQoL) and PQoL without mediation of fatigue assessed with FQ and CIS. A more cohesive framework needs to be developed with more comprehensive clinical tools for the different dimensions in the construct of CFS.